2010
DOI: 10.1007/s12072-010-9197-z
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study on sequence variations in the enhancer II/core promoter/precore and X genes of hepatitis B virus in patients with hepatocellular carcinoma

Abstract: Purpose To evaluate the sequence variations in the enhancer II (EnhII)/basal core promotor (BCP)/precore (PC) and X genes of hepatitis B virus (HBV) in Thai patients with hepatocellular carcinoma (HCC) by conducting a cross-sectional case-control study. Methods As much as 60 patients with HCC and 60 patients without HCC, who were matched for sex, age, hepatitis B e antigen (HBeAg) status, and HBV genotype, were included. Viral mutations in the EnhII/BCP/PC and X regions were characterized by direct sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Therefore, it is not surprising that T1753V is more frequently linked to HBV genotype C than genotype B (19.2% vs 1.9%; P = 0.013) [15] . G1899A combined with the BCP double mutation is the single risk factor indicating HCC risk in Thailand and Tunisia, but the linkages between mutations are less clear in South Korea [33,37,45,48] . Our data indicate that while G1896A increases steadily with time, the accumulation of A1846T begins to increase during the quadruple phase of mutations.…”
Section: Mutationmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, it is not surprising that T1753V is more frequently linked to HBV genotype C than genotype B (19.2% vs 1.9%; P = 0.013) [15] . G1899A combined with the BCP double mutation is the single risk factor indicating HCC risk in Thailand and Tunisia, but the linkages between mutations are less clear in South Korea [33,37,45,48] . Our data indicate that while G1896A increases steadily with time, the accumulation of A1846T begins to increase during the quadruple phase of mutations.…”
Section: Mutationmentioning
confidence: 98%
“…These effects can subsequently modulate the immune response to viral antigens and enhance the carcinogenic effects of altered X proteins [40] . In Far East Asia, HBV genotypes B and C are predominant, and five mutations are prominent in the core promoter and proximal precore regions: G1613A, C1653T, T1753V, A1846T, and G1899A [43][44][45][46][47] . These select mutations are associated with the development of HCC when combined with the BCP double mutation.…”
Section: Key Mutations In the Core Promoter And Proximal Precore Regimentioning
confidence: 99%
“…These studies included 1 study in Chinese and 10 in English (6,11,13,(16)(17)(18)(19)(20)(21)(22)(23). A detailed flow chart explaining the inclusion of studies is shown in Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Also, preSl and preS2 promoter mutations have been reported to be significandy higher in HCC patients (19.7 vs 3% and 15.3 vs 8.9%, respectively) [142]. Additionally, a precore mutation, G1899A, has been found to be significantly associated with HCC in Thailand [160,161]. …”
Section: Hbv-based Viral Dna Markersmentioning
confidence: 99%